(untitled) (Research, Society and Development, 2020)
The study aimed to identify the rate of falls in the elderly assisted by a Family Health Strategy in the municipality of Juazeiro do Norte/Ceará. This is a survey study carried out from February to May 2018 with 67 elderly people, selected for convenience. The elderly assisted by the selected FHS and who were at the health unit on the days and times previously scheduled for data collection were included. Those domiciled and restricted to the bed were excluded. A specific form was used as a data collection instrument with sociodemographic and interrogative questions directed to the occurrence of falls. It was found that the rate of falls of the participants was 44.77%, occurring in a greater proportion in males, older than 70 years, married, brown, illiterate and incomplete elementary school and retired. Thus, there is a need for greater care for the elderly, since the occurrence of falls is characterized as an additional risk factor for their health, and may also trigger functional, physical, cognitive and emotional problems that may interfere negatively in the performance of activities of daily living and, consequently, in their quality of life, with the ability to even lead to death.